Potential acaricide 2-Heptatone induces brain apoptosis and negatively affects survival in honey bees: comparison with thymol - Špela Golob; Janko Božič; Gordana Glavan (Ecotoxicology and Environmental Safety)
Varroa destructor is probably one of the greatest threats to honey bees. A potential natural acaricide, 2-heptanone (2 H) has shown promise in controlling mite populations in honey bee colonies, but the effects of prolonged systemic administration of 2 H on honey bee health remain unclear. In this study, we evaluated the effects of prolonged exposure to different concentrations of 2 H on honey bee (Apis mellifera carnica) survival, stress response, and neural system, comparing these effects with thymol. Sublethal effects were assessed by measuring the activity of two enzymes in bee heads and thoraces: acetylcholinesterase (AChE), which regulates neurotransmission, and glutathione S-transferase (GST), a detoxifying enzyme involved in the stress response. Brain cell death was assessed using the TUNEL assay. Carniolan honey bee workers were exposed to different concentrations of 2 H and thymol. Significant mortality caused by 2 H was observed starting at 0.8 ppm (w/v), while thymol-induced mortality was significant only at 25 ppm (w/v). Neither compound influenced GST activity. Thymol did not have any effect on the bee nervous system, whereas 2 H exhibited neurotoxic effects, inhibiting AChE activity at concentrations of 0.8, 1.2 and 1.6 ppm (w/v) and inducing apoptosis in the bee brain at a concentration of 1.2 ppm (w/v). The greater toxicity of 2 H compared to thymol, particularly regarding its negative neural effects and impact on survival at the tested concentrations, indicates that its use for mite control should be approached with caution and is not recommended under the specific exposure scenarios examined in this study.